Dust attenuation in galaxies at cosmic dawn from the FirstLight simulations - Mushtaq, Muzammil; Ceverino, Daniel; Klessen, Ralf S.; Reißl, Stefan; Hassan Puttasiddappa, Prajwal (Monthly notices of the Royal Astronomical Society, 2023)
We study the behaviour of dust in galaxies at cosmic dawn, z = 6-8, by coupling the FirstLight simulations with the radiative transfer code polaris. The starburst nature of these galaxies and their complex distribution of dust lead to a large diversity of attenuation curves. These follow the Calzetti model only for relatively massive galaxies, Mstars ≃ 109 M⊙. Galaxies with lower masses have steeper curves, consistent with the model for the Small Magellanic Cloud. The ultraviolet and optical slopes of the attenuation curves are closer to the modified Calzetti model, with a slight preference for the power-law model for galaxies with the highest values of attenuation. We have also examined the relation between the slope in the far-ultraviolet, βUV, and the infrared excess, IRX. At z = 6, it follows the Calzetti model with a shift to slightly lower βUV values due to lower metallicities at lower attenuation. The same relation at z = 8 shows a shift to higher IRX values due to a stronger CMB radiation at high z.